COVID-19 mRNA vaccination status and concerns among pregnant women in Japan: a multicenter questionnaire survey - Ken Takahashi; Osamu Samura; Akihiro Hasegawa; Haruna Okubo; Keiji Morimoto; Madoka Horiya; Aikou Okamoto; Daigo Ochiai; Mamoru Tanaka; Masaki Sekiguchi; Naoyuki Miyasaka; Yuto Suzuki; et al. (BMC, 2023)
Abstract Background mRNA vaccination is an effective, safe, and widespread strategy for protecting pregnant women against infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. However, information on factors such as perinatal outcomes, safety, and coverage of mRNA vaccinations among pregnant women is limited in Japan. Therefore, this study aimed to investigate the perinatal outcomes, coverage, adverse effects, and short-term safety of mRNA vaccination as well as vaccine hesitancy among pregnant women. Methods We conducted a multicenter online survey of postpartum women who delivered their offspring at 15 institutions around Tokyo from October 2021 to March 2022. Postpartum women were divided into vaccinated and unvaccinated groups. Perinatal outcomes, COVID-19 prevalence, and disease severity were compared between the two groups. Adverse reactions in the vaccinated group and the reasons for being unvaccinated were also investigated retrospectively. Results A total of 1,051 eligible postpartum women were included. Of these, 834 (79.4%) had received an mRNA vaccine, while 217 (20.6%) had not, mainly due to concerns about the effect of vaccination on the fetus. Vaccination did not increase the incidence of adverse perinatal outcomes, including fetal morphological abnormalities. The vaccinated group demonstrated low COVID-19 morbidity and severity. In the vaccinated group, the preterm birth rate, cesarean section rate, and COVID-19 incidence were 7.2%, 33.2%, and 3.3%, respectively, compared with the 13.7%, 42.2%, and 7.8% in the unvaccinated group, respectively. Almost no serious adverse reactions were associated with vaccination. Conclusions mRNA vaccines did not demonstrate any adverse effects pertaining to short-term perinatal outcomes and might have prevented SARS-CoV-2 infection or reduced COVID-19 severity. Concerns regarding the safety of the vaccine in relation to the fetus and the mother were the main reasons that prevented pregnant women from being vaccinated. To resolve concerns, it is necessary to conduct further research to confirm not only the short-term safety but also the long-term safety of mRNA vaccines.